Self-organizing systems : 6th IFIP TC 6 International Workshop, IWSOS 2012, Delft, The Netherlands, March 15-16, 2012. Proceedings - Heegaard, Poul E.; Kuipers, Fernando A. (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 6th IFIP TC 6 International Workshop on Self-Organizing Systems, IWSOS 2012, held in Delft, The Netherlands, in March 2012. The 5 revised full papers and 5 short papers presented together with 2 invited papers were carefully selected from 25 full paper and 8 short paper submissions. The papers address the following key topics: design and analysis of self-organizing and self-managing systems; inspiring models of self-organization in nature and society; structure, characteristics and dynamics of self-organizing networks; techniques and tools for modeling self-organizing systems; robustness and adaptation in self-organizing systems; self-organization in complex networks like peer-to-peer, sensor, ad-hoc, vehicular and social networks; control of self-organizing systems; decentralized power management in the smart grid; self-organizing group and pattern formation; self-organizing mechanisms for task allocation, coordination and resource allocation; self-organizing information dissemination and content search; and risks and limits of self-organization.